A comparison of maternal and neonatal outcomes of pregnant women with and without evidence of SARS-CoV-2 infection in the Western Cape, South Africa - Mudaly, Vanessa (Department of Public Health and Family Medicine, 2025)
Background: SARS-CoV-2 infection in pregnancy has been associated with poor pregnancy and neonatal outcomes. While SARS-CoV-2 infection itself could partly account for high maternal mortality rates observed in the Western Cape, indirect effects of the pandemic such as movement restrictions and health service pressure may also have played a role. There is limited data on the impact of having a SARS-CoV-2 diagnosis during pregnancy on maternal and neonatal outcomes in this setting. Objectives: We compared the characteristics and outcomes of pregnant women with and without a SARS-CoV-2 diagnosis with pregnancy outcomes between 1 March 2020 and 31 January 2022 within the Western Cape public healthcare sector. Methods: A retrospective cohort analysis was conducted using routine electronic data collated from public health sources. We compared demographic and clinical characteristics, pregnancy and maternal outcomes and neonatal outcomes by SARS-CoV-2 diagnosis status, gestational timing of diagnosis and by timing of pregnancy outcome during a COVID-19 wave to account for both direct and indirect effects of the pandemic. We used descriptive statistics, Chi-squared tests, Fisher Exact tests, and logistic regression models for analysis. Results: We included 226,336 pregnancies with 193,195 linked live births. Prevalence of a maternal SARS-CoV-2 diagnosis was 2.5%. Increased odds of SARS-CoV-2 diagnosis or hospitalization were associated with age categories ≥25 years compared to 15-24 years, pre- existing and gestational hypertension compared to no hypertension, pre-existing and gestational diabetes compared to no diabetes, current and previous tuberculosis compared to no tuberculosis and HIV positive status compared to HIV negative or unknown status. These factors would likely be more common in admitted patients where testing coverage was higher. In analyses adjusted for these factors, the odds of maternal death were higher in women with a SARS-CoV-2 diagnosis (aOR=11.42; 95% CI 8.46-15.43) than those without. The odds of miscarriage were higher with an early diagnosis (<28 weeks gestation) (aOR=2.18; 95% CI 1.91-2.48) and the odds of stillbirth were higher with a late diagnosis (≥28 weeks gestation) (aOR=1.31; 95% CI 1.02-1.67) compared to no diagnosis. Increased odds of low birth weight and neonatal intensive care unit (ICU) admission were found among infants of women who had a late SARS-CoV-2 diagnosis (aOR=1.22; 95% CI 1.10-1.34 and aOR=2.56; 95% CI 2.18-3.01, respectively) compared to infants of women without a SARS-CoV-2 diagnosis. Conclusion: This study found that that older age, diabetes, hypertension, current and previous tuberculosis and HIV were risk factors for a SARS-CoV-2 diagnosis or hospitalization in pregnancy during the COVID-19 pandemic period in our setting. Adverse outcomes associated with a maternal SARS-CoV-2 diagnosis included miscarriage, stillbirth, maternal death, low birth weight and neonatal ICU admission. However, it was not possible to determine the extent to which these outcomes were associated with SARS-CoV-2 infection itself, as SARS-CoV-2 testing was likely much higher in women admitted during pregnancy, and these outcomes would be strongly associated with admission. Nonetheless, these findings coupled with demonstrated benefits of COVID-19 vaccination, highlight the need to prioritise both pregnant women and women of child-bearing age for vaccination and boosting in order to maintain protective benefits.